Reconceptualizing Teacher Motivation: Integrating Herzberg’s Two-Factor Theory with Niat and Ikhlas in Islamic Education - Rusmini Rusmini; Saidah Saidah; Nispi Syahbani (STAI Syaichona Moh. Cholil Bangkalan, 2026)
This study aims to analyze the role of niat (religious intention) and ikhlas (sincerity) as spiritual motivators in the work motivation of madrasah teachers through the integration of Herzberg’s Two-Factor Theory with Islamic values. The study is grounded in the issue of low teacher welfare in madrasahs, which challenges the assumptions of conventional motivation theories that primarily emphasize material factors. This research employed a qualitative approach using Interpretative Phenomenological Analysis (IPA) involving 15 purposively selected informants from MTs An-Nizham Jambi City. Data were collected through interviews, observations, and documentation. The findings reveal that hygiene factors, such as low salaries and limited facilities, did not become the primary source of demotivation because they were compensated by spiritual orientations through niat lillahi ta‘ala and ikhlas. Niat functioned as an intrinsic motivation that provided transcendental meaning to teaching, while ikhlas served as a psychological-spiritual buffer in dealing with material limitations. This study extends Herzberg’s Theory by demonstrating that spirituality can function as a compensatory factor within faith-based organizations. The findings are also relevant for the development of human resource management in value-based and religious organizations.